2020
DOI: 10.3389/fimmu.2020.00357
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Dysbiosis and the Developing Lung: The Role of Toll-Like Receptor 4 in the Gut-Lung Axis

Abstract: Background: In extremely premature infants, postnatal growth restriction (PNGR) is common and increases the risk of developing bronchopulmonary dysplasia (BPD) and pulmonary hypertension (PH). Mechanisms by which poor nutrition impacts lung development are unknown, but alterations in the gut microbiota appear to play a role. In a rodent model, PNGR plus hyperoxia causes BPD and PH and increases intestinal Enterobacteriaceae, Gram-negative organisms that stimulate Toll-like receptor 4 (TLR4). We hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…At present, many studies have shown that the intestinal flora is closely associated with many diseases featuring chronic systemic inflammation ( 71 73 ). Intestinal bacteria not only influence immune and inflammatory responses at the local mucosal level but also lead to chronic pulmonary inflammation via gut-lung axis communication ( 52 , 74 ). Gut dysbiosis can lead to damage to intestinal mucosal barrier function and increase intestinal mucosal permeability ( 75 , 76 ); invading microorganisms and metabolites can cause local and systematic inflammation.…”
Section: Possible Mechanisms Of Gut Microbiota Causing Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…At present, many studies have shown that the intestinal flora is closely associated with many diseases featuring chronic systemic inflammation ( 71 73 ). Intestinal bacteria not only influence immune and inflammatory responses at the local mucosal level but also lead to chronic pulmonary inflammation via gut-lung axis communication ( 52 , 74 ). Gut dysbiosis can lead to damage to intestinal mucosal barrier function and increase intestinal mucosal permeability ( 75 , 76 ); invading microorganisms and metabolites can cause local and systematic inflammation.…”
Section: Possible Mechanisms Of Gut Microbiota Causing Lung Cancermentioning
confidence: 99%
“…For example, Stephen Wedgwood et al. found that gut dysbiosis characterized by a significant increase in Enterobacteriaceae activates TLR4 in the intestine and causes inflammation, increases the level of IL-1β in peripheral circulation, transduces inflammatory signals to the lungs, and activates the NF-κB pathway, leading to pulmonary inflammation ( 74 ). Similarly, Jia Tang et al.…”
Section: Possible Mechanisms Of Gut Microbiota Causing Lung Cancermentioning
confidence: 99%
“…In premature neonates, the association between hyperoxia and postnatal growth restriction, alters the microbiota of the distal small bowel and cecum, leading to an increase in pro-inflammatory Gram-negative Enterobacteriaceae: the recognition of lipopolysaccharide in the cell wall of Enterobacteriaceae by the host TLR-4 is important in the pathogenesis of necrotizing enterocolitis. TLR4 signaling is also involved in lung injury and inflammation (70). Moreover, hyperoxia might have a positive role during colon surgery.…”
Section: Gut and Bacterial Translocation Physiological Basismentioning
confidence: 99%
“…One possible reason is that hyperoxia alters the gut microbiota, leading to the pathogen invasion and inflammation involved in BPD development. For example, hyperoxia exposure dramatically elevated amounts ofEnterobacteriaceae 43 , Proteobacteria andEpsilonbacteraeota 44 in mouse intestines. Another murine intestinal tract showed that hyperoxia reversed the antibiotic-induced decreases in Bacteroidales andAlistipes and incerases ofAkkermansia 41 .…”
Section: Association Of Gut Microbiota With Bpdmentioning
confidence: 99%
“…For example, MAE increases the number of CD45-positive cells and granulocytes, leading to over-immunity, resulting in lung injury 38 . Besides this, metabolites produced by the gut microbiota, such as lipopolysaccharide, recognized by TLR4 via the pathogen-associated molecule patterns pathway, caused an increase in interleukin-1β, which further activated nuclear factor kappa-B and formed an inflammatory cascade leading to lung injury 43 . Surprisingly, gut microbiota and its metabolites also seem to be associated with pulmonary fibrosis 78 .…”
Section: Gut Microbiota Dysbiosis Promotes Inflammationmentioning
confidence: 99%